Hyperuricemia and the Risk of Heart Failure: Pathophysiology and Therapeutic Implications - Si, Ke; Wei, Chijing; Xu, Lili; Zhou, Yue; Lv, Wenshan; Dong, Bingzi; Wang, Zhongchao; Huang, Yajing; Wang, Yangang; Chen, Ying (Frontiers in Endocrinology, 2021)
The association between hyperuricemia and cardiovascular disease (CVD) has been reported and studied in the past two decades. Xanthine oxidase (XO) induced uric acid (UA) serves as a risk factor and has the independent prognostic and functional impact of heart failure (HF), but whether it plays a positive role in the pathogenesis of HF has remained unclear. Growing evidence suggest the up-regulated XO avtivity and increased production of free oxygen radical (ROS) correspondingly are the core pathogenesis of HF with hyperuricemia, which results in a whole cluster of pathophysiologic cardiovascular effects such as oxidative stress, endothelial dysfunction, vascular inflammation, left ventricular (LV) dysfunction as well as insulin resistance (IR). The use of XO inhibition represents a promosing therapeutic choice in patients with HF due to its dual effect of lowering serum UA levels as well as reducing ROS production. This review will discuss the pathophysiologic mechanisms of hyperuricemia with HF, the targeted therapeutic interventions of UA lowering therapies (ULT) with XO inhibition and mechanism underlying beneficial effects of ULT. In addition, the review also summarizes current evidence on the role of ULT in HF and compares CV risk between allopurinol and febuxostat for practical and clinical purposes. Guidelines and implementation of CV risk management in daily practice will be discussed as well.